Booklet 2.0 Sport fishing in the middle negro river, Barcelos, Amazonas, Brazil - Lubich, Chiara (Brasil, 2024)
This booklet is an invitation to you, the reader, to discover, support and value the sportfishing tourism carried out in the Middle Negro River Basin, Amazonas, Brazil. By betterunderstanding the diverse perspectives of the key groups and the results obtained inChiara Lubich's doctoral research, we can contribute to the promotion of sustainabletourism, for the benefit of the region, its population and the environment. Therefore, thebooklet aims to provide an understanding of the sustainability of sport fishing tourism inthe Negro River Basin, specifically in the region of Barcelos, Amazonas.Doctoral research project: The doctoral research project "Sport Fishing in the MiddleNegro River Basin, Amazonas, Brazil: Ecological, Economic and Social Assessment" seeksto holistically analyze the aspects and impacts of sport fishing tourism in the region. Theresearch is conducted by Chiara Lubich under the guidance of professors Carlos Freitasand Flávia Souza of the Graduate Program in Animal Science and Fisheries Resources atthe Federal University of Amazonas (PPGCARP/UFAM).